2014
DOI: 10.1039/c4en00018h
|View full text |Cite
|
Sign up to set email alerts
|

Sulfidation of copper oxide nanoparticles and properties of resulting copper sulfide

Abstract: International audienceMany nanoparticles (NPs) are transformed in the environment, and the properties of the transformed materials must be determined to accurately assess their environmental risk. Sulfidation is expected to alter the speciation and properties of CuO NPs significantly. Here, commercially available 40 nm CuO NPs were characterized and sulfidized in water by inorganic sulfide, and the properties of the resulting products were determined. X-ray absorption spectroscopy, X-ray diffraction, and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 42 publications
5
86
0
Order By: Relevance
“…Figure 3a depicts the diagram for the Cu-S system in water. In this case, the agreement of our calculation with the numerous available diagrams in the literature (e.g., [32,49,51,52]) is excellent, almost independently of the type of calculation (line or mass balanced methods) of the cited references. Concerning the defect Cu 2´x S species, they were not included in Brookins' [49] calculations, but the present results fully agree with the fields proposed by the other authors.…”
Section: Test Systems (Cu-o-h Sn-o-h Cu-s-o-h Sn-s-o-h)supporting
confidence: 58%
“…Figure 3a depicts the diagram for the Cu-S system in water. In this case, the agreement of our calculation with the numerous available diagrams in the literature (e.g., [32,49,51,52]) is excellent, almost independently of the type of calculation (line or mass balanced methods) of the cited references. Concerning the defect Cu 2´x S species, they were not included in Brookins' [49] calculations, but the present results fully agree with the fields proposed by the other authors.…”
Section: Test Systems (Cu-o-h Sn-o-h Cu-s-o-h Sn-s-o-h)supporting
confidence: 58%
“…3, the XANES spectra from Cu(NO 3 ) 2 , CuO‐NPs, and CuS‐NPs aged in the soils for 135 d are nearly identical to each other. It is worth noting that, despite their low K sp (6 × 10 −37 ), CuS‐NPs are susceptible to oxidative dissolution under aerobic conditions and are reportedly more soluble than CuO‐NPs (Ma et al, 2014). It has also been observed that, although Cu was found as various sulfides in freshly prepared biosolids, a significant proportion had transformed to HA or iron oxyhydroxide‐bound Cu after stockpiling (Donner et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Scenario B is based on the release of Ag NPs to wastewater from antimicrobial textiles and subsequent processing in a wastewater treatment plant where Ag particles are typically extensively if not completely sulfidized (WWTP) (Kaegi et al, 2011;Lombi et al, 2013;Ma et al, 2013b, Ma et al, 2014. In this scenario, surface affinity (α) of sulfidized PVPcoated Ag NPs to glass beads in a packed column is approximately two orders of magnitude smaller than that for unsulfidized PVPcoated Ag NPs (O'Brien unpublished data; see Supplemental Materials).…”
Section: Samples Of System Typesmentioning
confidence: 97%
“…One can follow the procedures used by many researchers: addition of NPs to the solution, brief sonication as needed, mixing on an orbital shaker for the duration of the test to minimize mass transfer resistance, and periodic measurements using centrifugal filtration with a 3 or 10 kDa filter to separate ions from NPs (Liu et al, 2010;Ma et al, 2012). Testing may eventually lead to the need for a larger MWCO filter that includes metal-macromolecule complexes in the "filterable/ bioavailable fraction" to be measured in the test (Ma et al, 2014;Li et al, 2015). These are simple batch tests adaptable to any type of solution that best represents the system of interest (e.g.…”
Section: Samples Of System Typesmentioning
confidence: 99%